Magnetic resonance‐transcranial ultrasound fusion imaging: A novel tool for brain electrode location. Issue 3 (12th September 2015) - Walter, Uwe; Müller, Jan‐Uwe; Rösche, Johannes; Kirsch, Michael; Grossmann, Annette; Benecke, Reiner; Wittstock, Matthias; Wolters, Alexander
ABSTRACT: Background: A combination of preoperative magnetic resonance imaging (MRI) with real‐time transcranial ultrasound, known as fusion imaging, may improve postoperative control of deep brain stimulation (DBS) electrode location. Fusion imaging, however, employs a weak magnetic field for tracking the position of the ultrasound transducer and the patient's head. Here we assessed its feasibility, safety, and clinical relevance in patients with DBS. Methods: Eighteen imaging sessions were conducted in 15 patients (7 women; aged 52.4 ± 14.4 y) with DBS of subthalamic nucleus (n = 6), globus pallidus interna (n = 5), ventro‐intermediate (n = 3), or anterior (n = 1) thalamic nucleus and clinically suspected lead displacement. Minimum distance between DBS generator and magnetic field transmitter was kept at 65 cm. The pre‐implantation MRI dataset was loaded into the ultrasound system for the fusion imaging examination. The DBS lead position was rated using validated criteria. Generator DBS parameters and neurological state of patients were monitored. Results: Magnetic resonance–ultrasound fusion imaging and volume navigation were feasible in all cases and provided with real‐time imaging capabilities of DBS lead and its location within the superimposed magnetic resonance images. Of 35 assessed lead locations, 30 were rated optimal, three suboptimal, and two displaced. In two cases, electrodes were re‐implanted after confirming their inappropriate location on computed tomography (CT) scan. No influence of fusion imaging on clinical state of patients, or on DBS implantable pulse generator function, was found. Conclusions: Magnetic resonance–ultrasound real‐time fusion imaging of DBS electrodes is safe with distinct precautions and improves assessment of electrode location. It may lower the need for repeated CT or MRI scans in DBS patients. © 2015 International Parkinson and Movement Disorder Society